Evaluasi Keberhasilan Implementasi Sistem Informasi Pelayanan Publik Menggunakan Pendekatan Technology Acceptance Model - Tutut Dwi Prihatin; Alva Hendi Muhammad; Tonny Hidayat (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The public service system in Tlagawera Village has used information technology in the form of a website called the Village Information System (SID). SID is a website that contains various village administration services such as; general administration, population administration, financial administration, service development administration, and other administrations. SID has yet to reach its potential, with most services still conducted offline. This triggered researchers to evaluate the effectiveness of SID to improve the quality of public services, in order to improve the quality of services of the Tlagawera Village Authority that supports responsive, transparent, and community-oriented governance. This research uses the Technology Acceptance Model (TAM) approach with the constituents used, namely External Variable, Perceived Usfulness, Perceived Ease of Use, Attitude Toward Using, Behavioural Intention to Use, Actual System Use. The study was conducted using 186 samples who were SID users using the Non-Probability Sampling method with the type of Purposive sampling. Data analysis using Particial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results showed that the important factor of External Variables had a positive effect on Perceived Usefulness, this was evidenced by the test results which showed the value of T-Statistcs which was 2.214 with P-Values 0.027. In addition, the Perceived Usefulness construct has a positive effect on Attitude Toward Using as evidenced by the test results that show the value of T-Statistcs is 68,769 with a P-Values of 0.000.   In addition, the construct of Perceived Usefulness has a positive effect on Behavioural Intention to Use, evidenced by theresults of hypothesis testing which shows a T-Statistcs value of 4,388 with a P-Values of 0,000. With the results obtained, it is concluded that the importance of external factors and perceptions of usefulness in increasing the acceptance and intention of using SID